PREVALENCE, PATHOGENESIS AND DIAGNOSIS OF SEXUAL DYSFUNCTIONS IN DIABETIC WOMEN - SAVITA DEVI,; KAMALDEEP SINGH,; PRANAY P PANKAJ, (International Journal of Pharma and Bio Sciences, 2016)
Diabetes mellitus is a chronic metabolic disorder in almost all countries. The secondary complications may include female sexual dysfunctions (FSDs) which are characterized by decreased libido, anorgasmia, dyspareunia and psycho-physiological disturbances. 40-60% FSDs cases are reported each year worldwide with increased late menopause period (42-88%), insufficient vaginal lubrication (5-28%), orgasmic disorder (5%) and dyspareunia (3-12%). Etiologies of FSDs are doubtful but certain physiological and psychological factors are involved in its contribution. The other risk factors for diabetes associated FSDs include cardiovascular disease, hypertension, genitourinary disease, psychological disorder, cancer and other chronic diseases. Subject’s histories with physiological and psychological attributes are the basis for FSDs diagnosis. Currently no specific treatment is available to treat FSD but its risk factors and complications may be controlled with the help of pharmacological, non-pharmacologic treatment and hormonal replacement therapy.